Accessible learning anytime anywhere: leveraging jotform tool to create course apps - Nordin, Azlin (KICT, 2025)
This article outlines a project from the KICT Teaching and Learning Exhibition 2025 that focuses on the "Tawhidic Paradigm in Teaching & Learning" by promoting Accessible Learning Anytime, Anywhere. The initiative addresses the barriers of relying solely on the university's Learning Management System (iTa'LeEM), such as login steps, occasional technical issues, and limited mobile-friendliness. The solution involves leveraging the JotForm tool to create a lightweight, mobile-friendly course app that provides students with quick, 24/7 access on any device to essential course materials like video lectures and slides , embodying the Islamic principle of amanah (knowledge as a trust) and ensuring equitable access to beneficial knowledge ('ilm nafi').